Financial Performance as Seen from The Angle of: Green Accounting, Environmental Performance, and Intellectual Capital in Major Energy Sector Companies Listed on The Indonesia Stock Exchange (Universitas Terbuka, 2025)
This study aims to investigate the effect of Green Accounting, Environmental Performance, and Intellectual Capital onl Financial Performance in primary energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. The study employs a quantitative approach with a causal research design. The quantitative method is used to systematically and objectively collect, process, analyze, and present data in order to test hypotheses. Causal research is applied to explain cause-and-effect relationships between GreenAccounting, Environmental Performance, and Intellectual Capital on Financial Performance. The population inl this study consists of 40 primary energy sector companies listed on the IDX. After applying eligibility criteria, 31 companies were selected as the sample. A total of 124 company-year observations were used throughout the research period. The results show lthat: (1) Green Accounting has a significant effect on Financial Performance; (2) Environmental Performance has no significant effect onl Financial Performance; (3)Intellectual Capital has a significant effect onl Financial Performance; and (4) Green Accounting, Environmental Performance, and Intellectual Capital simultaneously have asignificant effect on Financial Performance.